The current state of oil products in Ukraine - Любінін, Й.А.; Швидкий, О.А.; Щербініна, Л.О. (Proceedings of National Aviation University (archive), 2009)
Principal aspects as for the modern state of fuel and lubricating materials production in Ukraine had been considered.The information on crude oil supply to Ukrainian refineries, dynamics of its processing as well as fuel production for the period of 2003-2007 was presented. Analysis of oils, greases and metal working fluids production for the period of 2003−2007 was carried out.